A Search on the Importance of Forensic Voice Studies in Forensic and a Example Application - Bakir, Cigdem; Yuzkat, Mecit (IEEE, 2022)
In recent years, with the enormous development of technology, some security problems have emerged. One of these security problems is undoubtedly identification. Forensic voice examinations are carried out to ensure security by identifying. Because the protection of personal data of individuals, prevention of sharing with others, ensuring privacy by preventing the loss of valuable data are very important for the prevention of fraud, forgery and judicial crimes. In this study, research has been conducted on the importance of forensic today, its usage areas and examination of forensic voice. The general definition of forensic voice, its subject, common areas of use, methods used, studies and recent studies on forensic are discussed in detail. Improvement on sound, examination, identification from voice, speaker recognition, determination of spoken text covers the basic issues of forensic voice. For this reason, in order to set an example for the subject of forensic voice informatics, a sample application has been made that defines the speaker. In this application, approximately 5000 different lengths and the same texts were read and audio recordings were taken from 1000 people (5 voice recordings from each person). The attributes of the voice samples were obtained using MFCC (Mel Frequency Cepstral Coefficients). In this study, accuracy rates were calculated using different MFCC coefficients. The feature vectors of the obtained voice samples are trained with Convolutional Neural Networks. In the test phase, it was tried to determine who the voice sample belonged to by looking at the trained voice samples. In addition, the results and performances of the study are presented.
Keywords: forensic voice; security; identification; voice quality; voice enhancement; Computer Science; Engineering; Telecommunications